The picture of Dorian Gray : Il ritratto del male - Wilde, Oscar, 1854-1900 (Cult Media ; mHE, 2008)
Dorian Gray, a young charming and unscrupulous man, after being immortalized in a portrait, cannot tolerate the idea of getting old. He decides to make a deal with the Eval in order to preserve his appearance.